Music, dances, and videos: identity making and the cosmopolitan imagination in the southern Philippines - Canuday, J (2013)
This ethnography examines the processes in which rooted but overlapping forms of cosmopolitan engagements implicate the Tausug imagination of collectivity. It investigates Tausug expression of connection and belonging as they find themselves entangled into global cultural flow and caught up in the state and secessionist politics of attachment. Utilising methodological and theoretical approaches engendered by visual and material anthropology, the ethnography locates rooted cosmopolitan imagination in the works and lives of creative but marginalised and often silenced Tausug cultural agents engaged in street-based production, circulation, and consumption of popular music and dance videos on compact discs. The ethnography follows these cosmopolitan expressions as they are being imagined, embodied, reproduced, and shared by and across Tausug communities in the Zamboanga peninsula, the Sulu archipelago, and beyond through the digital spaces of the internet and cross-border flow of the videos. How the translocality of imaginaries reflected on the videos play out in everyday life and the broader politics of representation are demonstrated here as vital to the understanding of Tausug imagined community as an open, flexible, and dynamically engaging Muslim society despite long-standing political turbulence and economic uncertainty in their midst. Saliently, the thesis argues that Tausug cosmopolitanism cannot be reduced into a phenomenon driven by the expansive currents of Western-led globalisation. Rather, Tausug cosmopolitanism constitutes both continuity of and departure from past forms of translocal connections of Zamboanga and Sulu, which as a region was once integrated to a pre-colonial Southeast Asian emporium and continually through varying ways of connectedness. Old and new global processes come into play in shaping the everyday production of Tausug imaginaries inevitably rendering Tausug identity formation as a trajectory rather than an unchanging fact of being. Drawing from the Tausug ethnographic experience, the thesis contends that rooted cosmopolitanism does not necessarily constitute a singular condition but rather a contested and distinctively multifaceted phenomenon.